Morphological and histochemical analyses of two human T-cell subpopulations bearing receptors for IgM or IgG (The Rockefeller University Press, 1978)
Two subpopulation of circulating human T cells forming rosettes with neuraminidase-treated sheep erythrocytes were purified on the basis of the presence of receptors for IgG (TG cells) or for IgM (TM cells), and were shown to have distinguishing morphological and histochemical characteristics. TM cells had the general features of typical small- or medium-sized lymphocytes; most were easily identifiable by distinctive cytoplasmic accumulations, usually one and sometimes two large spots, of nonspecific acid esterase activity. The release of the vesicular contents on short-term culture of TG cells was inhibited by cytochalasin B. Definition of these distinguishing characteristics of TM and TG cells provides a basis for practical enumeration of these functionally distinct subpopulations of human T cells. Some of the TG cells were capable of endocytosis of IgG antibody-coated erythrocytes.